2022
DOI: 10.1096/fj.202200143r
|View full text |Cite
|
Sign up to set email alerts
|

Transient early life growth hormone exposure permanently alters brain, muscle, liver, macrophage, and adipocyte status in long‐lived Ames dwarf mice

Abstract: The exceptional longevity of Ames dwarf (DF) mice can be abrogated by a brief course of growth hormone (GH) injections started at 2 weeks of age. This transient GH exposure also prevents the increase in cellular stress resistance and decline in hypothalamic inflammation characteristic of DF mice. Here, we show that transient early‐life GH treatment leads to permanent alteration of pertinent changes in adipocytes, fat‐associated macrophages, liver, muscle, and brain that are seen in DF mice. Ames DF mice, like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 57 publications
4
18
0
Order By: Relevance
“…In studies by Aiello et al [2] and by Shindyapina et al [3], mice were treated in the phase of rapid growth, immediately after the birth, and rapamycin severely inhibited mouse growth. These studies revealed a "reprogramming window" during developmental growth [2,3], in agreement with studies in GH-deficient mice [47][48][49]. Similarly, for life extension, Daphnia magna was treated with rapamycin during developmental growth, resulting in a smaller body size [3].…”
Section: Two Approaches To Slow Aging With Rapamycinsupporting
confidence: 78%
See 1 more Smart Citation
“…In studies by Aiello et al [2] and by Shindyapina et al [3], mice were treated in the phase of rapid growth, immediately after the birth, and rapamycin severely inhibited mouse growth. These studies revealed a "reprogramming window" during developmental growth [2,3], in agreement with studies in GH-deficient mice [47][48][49]. Similarly, for life extension, Daphnia magna was treated with rapamycin during developmental growth, resulting in a smaller body size [3].…”
Section: Two Approaches To Slow Aging With Rapamycinsupporting
confidence: 78%
“…This reveals a "critical developmental time window" (a period of robust growth) that "programs" the rate of aging. In agreement, GH exposure during this period shortens lifespan [47,48]. Started at age of 2 weeks, administration of GH for a period of 6 weeks accelerated body growth and reverses longevity caused by GH deficiency [47,49].…”
Section: Growth Inhibition Decelerates Aging In Growth Hormone-defici...mentioning
confidence: 54%
“…The central finding of this report is that GPLD1 levels are elevated by genes, a diet, and four drugs that extend mouse lifespan. We have also found evidence for elevation of GPLD1 in two other kinds of long-lived mutant mice, i.e., Ames dwarf (Li et al, 2022), and PAPPA-KO mice (Li, X., Hager, M., McPherson, M., Lee, M., Hagalwadi, R., Skinner, M., Lombard, D., Miller, R. A., unpublished data). Thus, high GPLD1 seems to be characteristic of four varieties of long-lived mutants, four varieties of drug-treated mice, and calorically restricted mice.…”
Section: Sex-specific Elevation Of Gpld1 By Drugs That Increase Mouse...supporting
confidence: 53%
“…Ames mice treated transiently with GH also resemble wild-type, i.e. non-mutant, controls in adipose tissue UCP1 levels, relative ratios of pro-inflammatory and anti-inflammatory macrophages in adipose tissue, production of FNDC5 and its myokine cleavage product irisin by skeletal muscle, hepatic and plasma levels of GPLD1, and brain levels of protective factors BDNF and DCX [6],…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, these early-life GH injections block the development of multi-modal stress resistance shown by skin-derived fibroblasts of Ames dwarf mice [1], and also prevent the lower levels of hypothalamic inflammatory characteristic of unmanipulated Ames mice [2]. Many other characteristics of Ames dwarf mice, plausibly connected to their longevity, insulin sensitivity [3], and cognitive health [4, 5], are also blocked by early-life GH treatments when tested at 18 months of age, including changes in fat, muscle, plasma irisin and GPLD1, liver, and brain [6]. Conversely, lifespan can be increased in genetically normal mice by pre-weaning manipulation of litter size – mice weaned from litters in which litter size has been increased to 12 pups/nursing mother live longer than those in control litters of size 8 [7].…”
Section: Introductionmentioning
confidence: 99%